Promoting Restorative Justice in the Digital Era: Humanistic Management by the Takalar Police in Handling Minor Narcotics Offenders Based on Bugis-Makassar Cultural Values - Andi Aldiansyah; Mujahid Mujahid; Abdul Samad (Journal La Sociale, 2026)
Drug abuse, including minor offenses, is often handled with a repressive approach that results in imprisonment and exacerbates social stigma. This situation drives the need for a more humane law enforcement strategy through restorative justice, especially amidst the dynamics of the digital era. This study aims to describe the Takalar Police's humane strategy in implementing restorative justice in the digital era to address minor drug offenders, based on Bugis-Makassar cultural values (sipakainge, sipakatau, and sipakalebbi). This study aims to describe the Takalar Police's humanist strategy in implementing restorative justice socialization in the digital era to address minor drug abusers based on Bugis-Makassar cultural values (sipakainge, sipakatau, and sipakalebbi). This research was conducted at the Takalar Police Headquarters. Data collection was conducted through observation, in-depth interviews, and documentation. Data analysis used qualitative methods with a narrative or descriptive qualitative study approach. The results of the study indicate that the Takalar Police's humanist strategy emphasizes the recovery and social reintegration of perpetrators through a deliberation approach, coaching, and strengthening family/community support, while internalizing the values of sipakainge, sipakatau, and sipakalebbi as an ethical foundation in treating perpetrators with dignity. In the context of the digital era, the use of technology also supports the effectiveness and accountability of the process, including through application-based rehabilitation monitoring and strengthening information transparency to the public through digital platforms.